(3GdQSGdI GdHgGFjI aj GdMSGHs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3GdejGJ hgj ef eGjI Edi JSYeGjg HRjGOI eGjI hefRdJgG GdKGdKI hGdaQYjI eG ajgG s
(3BNQgG (B:s
(3hdh cGf bUjOkG hEfeG CWfHJG ai gPG GdebUO CYfi Yde GdRGjQLI hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HBNQg fbhd eNJdaIs
(3HgG Jedc HGSe edG YHO Gddg GdYHO di Ydi ChdGOg hJQLY dSfg (B1239 (3g`s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdeLGejYs